2009
DOI: 10.1007/s12289-009-0665-8
|View full text |Cite
|
Sign up to set email alerts
|

Some considerations regarding finishing by abrasive flap wheels

Abstract: The diminishing of the surface roughness of a metallic part can be performed by using various finishing methods, polishing by means of abrasive flap wheels being one of them. There are several factors that influence the roughness of surfaces finished by means of abrasive flap wheels. When polishing external cylindrical surfaces by means of abrasive flap wheels, the surface roughness can be changed more easily if the following elements are modified: the peripheral speed of the workpiece and of the abrasive flap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Considerable studies have been carried out to investigate the work surface roughness induced by the flap wheel grinding process [1][2][3][4][5]. They can be concluded that the rotational speed, applied pressure, hardness of abrasive particles and cooling method can affect the surface roughness obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable studies have been carried out to investigate the work surface roughness induced by the flap wheel grinding process [1][2][3][4][5]. They can be concluded that the rotational speed, applied pressure, hardness of abrasive particles and cooling method can affect the surface roughness obtained.…”
Section: Introductionmentioning
confidence: 99%
“…There are different varieties of flap wheels, where foambased flaps, non-woven type flaps, etc. are available [16,17] . Belt type finishing is one of the common polishing used in industries, robot or CNC assisted to polish complex 3D parts [18,19].…”
Section: Types Of Coated Abrasive Polishing Toolsmentioning
confidence: 99%
“…Umer et al [27] created FEA models to investigate the compliance effect of glass fibre backing pad. Since the glass fibre 16 disc is considerably stiffer compared to other flexible tools, the disc was assigned elastic material property. The load-displacement and contact pressure distribution as shown in Figure 2.6 (b) were obtained from simulations and compared with the experimental values.…”
Section: Contact Pressure Distribution In Compliant Polishing Toolsmentioning
confidence: 99%